A Community-Linked Model for the Management of Children’s Mental and Physical Health - Niu, Peilin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
With the rise of exercise psychology, the society is attaching greater importance to the physical and mental health of children and youngsters. If sports intervention is implemented persistently, children and youngsters will have a tougher mind, a higher confidence, and a stronger resistance to setbacks. However, the relevant literature lacks quantitative analysis, and fails to study the mediating effect of sports perseverance mechanism. Thus, this paper explores the cultivation and regression analysis of children’s mental toughness under the intervention of sports perseverance mechanism. Firstly, a model was established to analyze the sports perseverance intervention facing children’s mental toughness. Next, a multi-factor cointegration test was performed on the time series of the quantified values of children’s mental toughness under the intervention of sports perseverance. In addition, the error correction model and breakpoint regression model were constructed to determine the moments that the time series deviate from the equilibrium state and return to the normal state. The test results of the proposed models were obtained through experiments, which verify the effectiveness of these models.